Diagnostics and Policy Advice on the Integration of Roma in the Slovak Republic - World Bank (Washington, DC, 2014)
This report is meant to support the Slovak Government in its efforts to address the exclusion of the Roma by offering evidence-based policy advice. The assessment relies on three main sources of information. First, it takes advantage of the 2011 United Nations Development Programme (UNDP)/World Bank/EC regional Roma survey, described, which is the most comprehensive survey effort to date to capture the situation of marginalized Roma in Central and Eastern Europe. It also includes information from the 2010 survey by UNDP, done specifically on Slovak Roma at the request of the ministry of labor, social affairs, and family. The results on comparable indicators from both surveys are very similar. Second, this report relies on qualitative information, collected through field visits in Eastern Slovakia and through interviews with key stakeholders from the Slovak Government and from civil society. And third, each of the chapters highlights relevant international experiences from which Slovak policy formulation on Roma integration can benefit. Many of the international examples and best practices from integrating poor and marginalized communities elsewhere provide reasons to be optimistic that Roma integration does not have to be a distant goal for Slovakia. The remainder of this report provides an overview of the assessment of the situation in five sectors and in two cross-cutting areas, followed by specific policy recommendations in each. These five sectors are: (1) employment and social protection, (2) financial inclusion, (3) education, (4) housing, and (5) health, while the cross-cutting areas are (6) monitoring and evaluation, and (7) use of EU financing instruments. One critical area beyond the scope of this report is the ability of the Slovak legal and judicial system to successfully protect the rights of all citizens, including the courts, issues of legal aid, as well as law enforcement issues. Recently, a much discussed court ruling in Eastern Slovakia held school segregation as illegal. More of such cases may emerge, especially in light of the 2007 ruling against school segregation by the European Court of Human Rights in Strassbourg. While important, these are all beyond the scope of this report.